PENGARUH PENERAPAN METODE PEMBELAJARAN COURSE REVIEW HOREY TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII MTsN TALAOK KECAMATAN BAYANG PESISIR SELATAN - Sari, Yanti Menda (STKIP PGRI Sumbar, 2014)
This research was background by studying result for students in class VIII MTsN Talaokis still low. The learning method which is used by the teacher hasnât still been variation so thatmake the student motivation in learning still low. This research has purpose to know the influenceof implementing learning method course review horey for the result of Biology for student classVIII MTsN Talaok. The type of this research is experiment by research design RandomizedControl-Group posttest Only Design. The population is all students in class VIII MTsN Talaokyear 2014/2015. The technique for taking the sample is done Purposive sampling. To decideexperiment class and control class which is used random sampling so class VIII.7 was the choiceas experiment and class VIII.6 as the control class. The data analysis technique has purpose to testhypothesis which is aim whether accepted or refused. The result of research can be gotten inexperiment class was gotten the average that 78,429 and control class gotten the average 69,423.The hypothesis testing use test-t gotten thitung 2,4262 is greater than ttabel 1,674, so the hipotesiswhich is used accepted. The conclusion that learning method course review horey can increasebiology result of students in class VIII MTsN Talaok Kecamatan Bayang, Pesisir Selatan.